0393 Baseline Pain Severity as a Moderator of the Effect of CBTi on Sleep and Pain Outcomes in Patients with Fibromyalgia. (12th April 2019) - McCrae, Christina; Curtis, Ashley; Staud, Roland; Berry, Richard; Robinson, Michael
Abstract: Introduction: CBTi improves sleep and pain in patients with chronic pain, but significant pain effects are rarely found in individual trials - possibly due to floor effects as trials rarely screen for baseline pain intensity (bPI). The present study examines whether bPI moderates the effect of CBTi on sleep and pain in adults with FM. Methods: Adults (N=64, Mage =53.2, SD=13.7) with FM and chronic insomnia were randomized to 8-week CBT-I or waitlist control. Participants completed the McGill Pain Questionnaire (MPQ) and 14 daily diaries recording PI (0-none, 100-worst), SOL, WASO, TWT, and sleep quality (1-very good, 5-very poor) at baseline, post-treatment, and 6-month follow-up. Multiple regressions determined whether average bPI predicted changes in sleep (SOL, WASO, TWT, sleep quality) and pain (MPQ total score), controlling for age, sleep/pain medication, TST, and depression. Results: bPI moderated the impact of CBTi on SOL (t=2.42, p=.02) and TWT (t=2.02, p=.05). Specifically, moderate (53.32, SOL t=2.43, p=.02; TWT t=3.18, p<.001) and high (71.18, SOL t=3.68, p<.001; TWT t=3.96, p<.001) bPI were associated with improved SOL and TWT at post-treatment relative to baseline, whereas these associations were not observed for low bPI (35.80, SOL p=.96, TWT p=.37). bPI trended toward significance for the MPQ (p=.06) and WASO (p=.11), but did not moderate changes in sleep quality. Baseline to follow-up results were similar. Conclusion: FM patients with moderate to severe pain may be better candidates for CBTi than those with less severe pain. Clinical trial researchers may wish to consider adopting pain severity criteria for determining eligibility for CBT trials. While our findings suggest a score of 50/100 may identify patients likely to benefit from CBTi, research is needed to determine the best screening cutoff score and to identify better treatment options for chronic pain patients with less severe pain. Support (If Any): NIAMS (R01AR055160 and R01AR005160-S1; McCrae, PI). Data collected as part of clinical trial NCT02001077 Sleep and Pain Interventions (SPIN) at the University of Florida (McCrae, PI).